Assessing the Role of China’s Investment on Youth Empowerment in South Africa - Kenalemang Mokoena (Journal of BRICS Studies, 2024)
China is indeed the biggest investor in South Africa but it is very important to understand the effects that its investment has on the youth of South Africa. This study aims to analyse whether China's investment empowers the youth of South Africa through entrepreneurial skills, access to advanced technology, and provisions of scholarships. The findings of the study reveal that there is a level of inconsistency when it comes to China empowering the youth of South Africa. The study, therefore, recommends that China's relationship with South Africa should prioritize the youth of South Africa and be consistent in do so to contribute to their development as individuals.